L’avantage mutuel. Recherche-action sur le retour et le maintien en activité de salariés touchés par une maladie chronique - Guillaume Huyez-Levrat; Anne-Marie Waser (La Nouvelle Revue du Travail)
We use action research conducted in a non-food-sector trading company to highlight the kinds of arrangements culminating in job retention for employees weakened by chronic illness and its enabling factors.Chronic illness is a vague reference to people’s inability to work under habitual circumstances. This can be highly variable over time, however, with great uncertainty about how things might evolve in the future.Hence the idea that responses to the kinds of imbalances that chronic illness inflicts upon the organisation of work must supersede institutional systems mainly developed to deal with disabilities categorised administratively as industrial accidents and occupational health problems.In turn, this presumes a justification of whatever arrangements are actually developed. Such efforts specifically apply to workers suffering ill health and who must show their peers that they are worthy of the arrangements in question.